BS EN 60601-1-3 AMD2. Medical electrical equipment. Part 1-3. General requirements for basic safety and essential performance. Collateral Standard: Radiation protection in diagnostic X-ray equipment (7th August 2020) - British Standards Institution,
No abstract available